Carotid endarterectomy or stenting or best medical treatment alone for moderate-to-severe asymptomatic carotid artery stenosis: 5-year results of a multicentre, randomised controlled trial. Issue 10 (October 2022) - Reiff, Tilman; Eckstein, Hans-Henning; Mansmann, Ulrich; Jansen, Olav; Fraedrich, Gustav; Mudra, Harald; Böckler, Dittmar; Böhm, Michael; Debus, E Sebastian; Fiehler, Jens; Mathias, Klaus; Ringelstein, Erich B; et al.
Summary: Background: The optimal treatment for patients with asymptomatic carotid artery stenosis is under debate. Since best medical treatment (BMT) has improved over time, the benefit of carotid endarterectomy (CEA) or carotid artery stenting (CAS) is unclear. Randomised data comparing the effect of CEA and CAS versus BMT alone are absent. We aimed to directly compare CEA plus BMT with CAS plus BMT and both with BMT only. Methods: SPACE-2 was a multicentre, randomised, controlled trial at 36 study centres in Austria, Germany, and Switzerland. We enrolled participants aged 50–85 years with asymptomatic carotid artery stenosis at the distal common carotid artery or the extracranial internal carotid artery of at least 70%, according to European Carotid Surgery Trial criteria. Initially designed as a three-arm trial including one group for BMT alone (with a randomised allocation ratio of 2·9:2·9:1), the SPACE-2 study design was amended (due to slow recruitment) to become two substudies with two arms each comparing CEA plus BMT with BMT alone (SPACE-2a) and CAS plus BMT with BMT alone (SPACE-2b); in each case in a 1:1 randomisation. Participants and clinicians were not masked to allocation. The primary efficacy endpoint was the cumulative incidence of any stroke or death from any cause within 30 days or any ipsilateral ischaemic stroke within 5 years. The primary safety endpoint was any stroke or death from any cause within 30 days after CEA or CAS. The primary analysis was by intention-to treat, which included all randomly assigned patients in SPACE-2, SPACE-2a, and SPACE-2b, analysed using meta-analysis of individual patient data. We did two-step hierarchical testing to first show superiority of CEA and CAS to BMT alone then to assess non-inferiority of CAS to CEA. Originally, we planned to recruit 3640 patients; however, the study had to be stopped prematurely due to insufficient recruitment. This report presents the primary analysis at 5-year follow-up. This trial is registered with ISRCTN, number ISRCTN78592017. Findings: 513 patients across SPACE-2, SPACE-2a, and SPACE-2b were recruited and surveyed between July 9, 2009, and Dec 12, 2019, of whom 203 (40%) were allocated to CEA plus BMT, 197 (38%) to CAS plus BMT, and 113 (22%) to BMT alone. Median follow-up was 59·9 months (IQR 46·6–60·0). The cumulative incidence of any stroke or death from any cause within 30 days or any ipsilateral ischaemic stroke within 5 years (primary efficacy endpoint) was 2·5% (95% CI 1·0–5·8) with CEA plus BMT, 4·4% (2·2–8·6) with CAS plus BMT, and 3·1% (1·0–9·4) with BMT alone. Cox proportional-hazard testing showed no difference in risk for the primary efficacy endpoint for CEA plus BMT versus BMT alone (hazard ratio [HR] 0·93, 95% CI 0·22–3·91; p=0·93) or for CAS plus BMT versus BMT alone (1·55, 0·41–5·85; p=0·52). Superiority of CEA or CAS to BMT was not shown, therefore non-inferiority testing was not done. In both the CEA group and the CAS group, five strokes and no deaths occurred in the 30-day period after the procedure. During the 5-year follow-up period, three ipsilateral strokes occurred in both the CAS plus BMT and BMT alone group, with none in the CEA plus BMT group. Interpretation: CEA plus BMT or CAS plus BMT were not found to be superior to BMT alone regarding risk of any stroke or death within 30 days or ipsilateral stroke during the 5-year observation period. Because of the small sample size, results should be interpreted with caution. Funding: German Federal Ministry of Education and Research (BMBF) and German Research Foundation (DFG).